Consider the equation x 2 + p x + q = 0 x^2 + px + q = 0 x 2 + p x + q = 0 , where p p p and q q q are positive numbers. (Math problems are always asking you to "consider" something.) If the roots of this equation differ by 1, then p p p equals:
4 q + 1 \sqrt{4q+1} 4 q + 1
q − 1 q-1 q − 1
− 4 q + 1 -\sqrt{4q+1} − 4 q + 1
q + 1 q+1 q + 1
4 q − 1 \sqrt{4q-1} 4 q − 1
Solution Here we go: x 2 + p x + q = 0 → x = − p ± p 2 − 4 q 2 x^2 + px + q = 0 \rightarrow x = \dfrac{-p \pm \sqrt{p^2-4q}}{2} x 2 + p x + q = 0 → x = 2 − p ± p 2 − 4 q . If these two roots differ by 1, then
1 = − p + p 2 − 4 q 2 − − p − p 2 − 4 q 2 = − p + p 2 − 4 q 2 + p + p 2 − 4 q 2 = 2 p 2 − 4 q 2 = p 2 − 4 q \begin{align*}1 &= \dfrac{-p + \sqrt{p^2-4q}}{2} - \dfrac{-p - \sqrt{p^2-4q}}{2} \\[1em]&= \dfrac{-p + \sqrt{p^2-4q}}{2} + \dfrac{p + \sqrt{p^2-4q}}{2} \\[1em]&= \dfrac{2\sqrt{p^2-4q}}{2} \\[1em]&= \sqrt{p^2-4q}\end{align*} 1 = 2 − p + p 2 − 4 q − 2 − p − p 2 − 4 q = 2 − p + p 2 − 4 q + 2 p + p 2 − 4 q = 2 2 p 2 − 4 q = p 2 − 4 q
So p 2 − 4 q = 1 → p 2 − 4 q = 1 → p 2 = 4 q + 1 → p = 4 q + 1 \sqrt{p^2-4q} = 1 \rightarrow p^2-4q = 1 \rightarrow p^2 = 4q+1 \rightarrow p = \sqrt{4q+1} p 2 − 4 q = 1 → p 2 − 4 q = 1 → p 2 = 4 q + 1 → p = 4 q + 1 (p p p was given as positive.)
So it's (a).
You might verify this by building a quadratic that fits, e.g. ( x + 2 ) ( x + 3 ) (x+2)(x+3) ( x + 2 ) ( x + 3 ) .